One informs the other: Unionid species at risk and benthic macroinvertebrate community monitoring data are complementary - Roland A. Eveleens; Todd J. Morris; Daelyn A. Woolnough; Catherine M. Febria (Canadian Science Publishing, 2023)
Benthic macroinvertebrate communities, which include unionid freshwater mussels, enhance the health of river ecosystems. Human impacts have driven declines within freshwater mussel communities and due to their complex life cycles, mussel recovery efforts are complex. In Canada, conservation of imperiled species has focused on biodiversity hotspots such as the Sydenham River in the Laurentian Great Lakes Basin. In practice, species conservation and habitat monitoring are siloed between federal agencies and local conservation authorities, limiting the potential for alignment of conservation policy and practice. Here we bring together federal, local, and our own survey data to explore patterns of co-occurrences between mussel species and other macroinvertebrate taxa to explore the extent to which knowledge of one benthic community informs the other. Mussel communities (species richness, community composition) differed between sites where imperiled mussel species were present and/or absent. Benthic macroinvertebrate metrics (e.g., family richness, percent Ephemeroptera, Plecoptera, and Trichoptera taxa) and specific indicator taxa were correlated with mussel species richness and the presence of imperiled mussel species. We show that benthic macroinvertebrate diversity indicators provided insight into imperiled species occurrences that warrant further investigation. These findings underscore support for coordinated watershed monitoring efforts and could be crucial for more successful freshwater mussel conservation.